2006
DOI: 10.1111/j.1538-7836.2006.02039.x
|View full text |Cite
|
Sign up to set email alerts
|

Main haplotypes and mutational analysis of vitamin K epoxide reductase (VKORC1) in a Swedish population: a retrospective analysis of case records

Abstract: Summary. Background: Vitamin K epoxide reductase (VKORC1) is the site of inhibition by coumarins. Several reports have shown that mutations in the gene encoding VKORC1 affect the sensitivity of the enzyme for warfarin. Recently, three main haplotypes of VKORC1; *2, *3 and *4 have been observed, that explain most of the genetic variability in warfarin dose among Caucasians. Objectives: We have investigated the main haplotypes of the VKORC1 gene in a Swedish population. Additional objective was to screen the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 33 publications
5
45
0
2
Order By: Relevance
“…This variability being partly due to genetic polymorphisms in the Vkorc1 gene, numerous studies have been performed to detect new Vkorc1 mutations in patients resistant to AVK. These studies allowed to detect in humans 27 mutations in the coding sequence of the Vkorc1 gene (Bodin, Horellou, Flaujac, Loriot, & Samama, 2005; Bodin, Perdu, Diry, Horellou, & Loriot, 2008; D'Andrea et al., 2005; Harrington, Siddiq, Allford, Shearer, & Mumford, 2011; Harrington et al., 2008; Loebstein et al., 2007; Osman, Enström, Arbring, Söderkvist, & Lindahl, 2006; Peoc'h, Pruvot, Gourmel, Dit Sollier, & Drouet, 2009; Rieder et al., 2005; Rishavy, Usubalieva, Hallgren, & Berkner, 2011; Rost et al., 2004; Schmeits et al., 2010; Watzka et al., 2011; Wilms, Touw, Conemans, Veldkamp, & Hermans, 2008). In rats, 15 missense mutations in the Vkorc1 gene of Rattus norvegicus have been described in Europe (Grandemange, Lasseur, Longin‐Sauvageon, Benoit, & Berny, 2010; Haniza et al., 2015; Pelz et al., 2005, 2012; Rost et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This variability being partly due to genetic polymorphisms in the Vkorc1 gene, numerous studies have been performed to detect new Vkorc1 mutations in patients resistant to AVK. These studies allowed to detect in humans 27 mutations in the coding sequence of the Vkorc1 gene (Bodin, Horellou, Flaujac, Loriot, & Samama, 2005; Bodin, Perdu, Diry, Horellou, & Loriot, 2008; D'Andrea et al., 2005; Harrington, Siddiq, Allford, Shearer, & Mumford, 2011; Harrington et al., 2008; Loebstein et al., 2007; Osman, Enström, Arbring, Söderkvist, & Lindahl, 2006; Peoc'h, Pruvot, Gourmel, Dit Sollier, & Drouet, 2009; Rieder et al., 2005; Rishavy, Usubalieva, Hallgren, & Berkner, 2011; Rost et al., 2004; Schmeits et al., 2010; Watzka et al., 2011; Wilms, Touw, Conemans, Veldkamp, & Hermans, 2008). In rats, 15 missense mutations in the Vkorc1 gene of Rattus norvegicus have been described in Europe (Grandemange, Lasseur, Longin‐Sauvageon, Benoit, & Berny, 2010; Haniza et al., 2015; Pelz et al., 2005, 2012; Rost et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this is a Swedish study showing the association between the maintenance dosage of warfarin and several VKORC1 genetic polymorphisms (1413 A > G, intron 1 136 C > T, intron 2+837 T > C, and exon 343 G > A). 27) Moreover, Yuan, et al, showed that VKORC1 1413 A > G polymorphism may explain why the Chinese require lower maintenance warfarin dosages than Caucasians. 28) Mushiroda, et al proposed the WRI, which allocates a number to particular combinations of CYP2C9 and VKORC1 SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…57 The found that patients with VKORC1*2 haplotype (similar to haplotype A, using the nomenclature of Rieder et al 55 ) had lower warfarin doses and lower therapeutic warfarin levels than other patients. Furthermore, these patients also had a higher percentage of INR values outside the therapeutic interval.…”
Section: Snps In Vkorc1 Correlate With Warfarin Dosementioning
confidence: 99%